Metaverse Technology and Criminal Law - BENSALEM, Ahmed Abderrahman; BENSADOK, Ahmed; GHARBI, Ali (Journal of Human Sciences, 2025)
Metaverse technology represents a paradoxical concept, both mysterious and divided within itself, as it simultaneously suggests reality and non-reality, truth and falsehood. It merges real life with virtual and augmented reality, creating a significant impact across social, economic, technological, and even legal domains. Given that the law is one of these affected areas, it necessitates a pragmatic and realistic integration of all technological data under a thorough legal framework. Despite the difficulties and their impact on the structure and content of the legislation, this research paper aims to address the Metaverse from a legal perspective, specifically focusing on criminal law.